Analisis Pengaruh Belanja Pemerintah Daerah terhadap Pertumbuhan Ekonomi di Kabupaten Kepulauan Yapen Tahun 2012-2022 - Waspada Meliala; Virgilio cancera Meliala (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Poverty is not just about difficulties in meeting basic needs, but also involves various dimensions of human life such as health, education, future security, and influential social roles. Some factors that influence poverty include the Gender Development Index (GDI), the Human Development Index (HDI), and Economic Growth as measures of human progress and economic development. In this study, the path analysis method is used, allowing us to identify the direct and indirect impacts of independent variables on dependent variables. Thus, we can understand the complex relationship between various factors in the context of poverty. The information used for this study is sourced from the Central Statistics Agency of Central Kalimantan using secondary information in the form of time series data. The findings of this research show that the gender development index has no influence on the economic growth variable. The human development index also does not affect the economic growth variable. Additionally, the gender development index does not affect the poverty level variable. However, the human development index significantly affects the economic growth variable. Meanwhile, economic growth does not affect the poverty level. Finally, the human development index through economic growth does not have a significant impact on the poverty level.